An investigation of investors' exposure towards stock market and preferred investment avenues: A study in Krishna District - Madanu, Bala Swamy; Nagaraj, K V (Indonesian Journal Publisher, 2024)
Money is an important component of living in the current era. People must invest their money to solve future difficulties. Investment is a commitment of funds set aside from current expenses in anticipation of future gains. Savings are invested in assets based on an individual's knowledge of numerous investment options, risk tolerance, and expected return. Every human being must take the vital step of investing hard-earned money. Investors can put their money into a variety of investment vehicles. Each of these investment ideas carries a distinct level of risk and potential return. Investors anticipate bigger returns with less risks. Financial consultants and advisors give a wide range of suggestions to investors in this field. However, every investor faces a difficult task when putting together an appropriate portfolio. The investing possibilities cover both financial instruments and other assets. Investor attitudes may vary throughout time and from person to person. Additionally, investors' investment objectives will vary.